How to diagnose mould allergy? Comparison of skin prick tests with specific IgE results. Issue 7 (3rd May 2016) - Kespohl, S.; Maryska, S.; Bünger, J.; Hagemeyer, O.; Jakob, T.; Joest, M.; Knecht, R.; Koschel, D.; Kotschy‐Lang, N.; Merget, R.; Mülleneisen, N. K.; Rabe, U.; et al.
Summary: Background: Diagnosis of mould allergy is complicated due to the heterogeneity of the test material and the decrease in the number of commercial mould skin test solutions that are currently available. Objectives: The aim of this study was to compare skin prick tests (SPT) from different manufacturers to one another and concurrently with sIgE tests for Aspergillus fumigatus (Asp f), Cladosporium herbarum (Cla h), Penicillium chrysogenum (Pen ch), Alternaria alternata (Alt a) and Aspergillus versicolor (Asp v) to ascertain a feasible diagnostic procedure for mould sensitization. Methods: In this multi‐centre study, 168 patients with mould exposure and/or mould‐induced respiratory symptoms were included. Mould SPT solutions were analysed biochemically and tested in duplicate on patients' arms. Specific IgE (sIgE) concentrations to corresponding mould species and mould mix (mx1) were measured by ImmunoCAP. SPTs in accordance with one another and with sIgE were further considered. The test efficiency was calculated using receiver‐operating characteristic (ROC) analysis. Results: Mould sensitization was more frequently detected by the SPT (90 of 168) than by the sIgE tests (56 of 168). Concordances of double SPT positives were only sufficient (≥ 80%) for environmental allergens, two Asp f and three Alt a SPT solutions, whereas all other mould solutions revealed concordances < 80%. The antigen content of SPT solutions was positively associated with concordant SPT double values as well as with sIgE. Taking sIgE as the 'positive standard', all mould SPT solutions revealed test efficiencies > 80%, but varied up to 20% in sensitivity and positive predictive value with the exception of Alt a. Conclusions: SPT solutions are sensitive and essential diagnostic tools for the detection of mould sensitization. Our recommendation for diagnosis would be to test at least Alt a, Asp f and Pen ch using SPT and additional sIgE test to mx1.